Allergic contact dermatitis in children: “emerging allergens”. - Romita, P.; Foti, C.; Bonamonte, D. (European Journal of Pediatric Dermatology, 2020)
This letter aims to draw the attention of dermatologists and pediatricians to certain emerging allergens that may cause allergic contact dermatitis (ACD) in children. Allergic contact dermatitis is an inflammatory skin disease, that is a cell-mediated hypersensitivity reaction (type IV) to exogenous antigens. The diagnosis is made by patch testing. As reported in literature, the tests may occasionally result positive to “emerging” allergens in the general population or peculiar population, as for fragrances in atopic children.